Post-donation satisfaction in kidney transplantation: a survey of living donors in Japan - Sayaka Kobayashi; Rie Akaho; Kazuya Omoto; Hiroki Shirakawa; Tomokazu Shimizu; Hideki Ishida; Kazunari Tanabe; Katsuji Nishimura (BMC, 2019)
Abstract Background No studies using a valid, standardized method to measure post-donation satisfaction levels among living kidney donors (LKDs) have been published. Methods Donor satisfaction levels were measured using the Japanese version of the Client Satisfaction Questionnaire-8 (CSQ-8), a validated, self-report questionnaire. To identify factors related to post-donation satisfaction levels, we compared donors' sociodemographic and psychological characteristics and health-related quality of life (HRQoL), using the Short Form-36 Health Survey (SF-36), as well as recipients' clinical characteristics and SF-36 scores between donors with and without low satisfaction. In addition, donors' perceptions of the donation results and transplant procedure were assessed using measures that we developed. Results The mean (standard deviation [SD]) CSQ-8 score for the 195 participants was 26.9 (3.4). Twenty-nine (14.9%) respondents with total scores < 1 SD below the mean CSQ-8 score were placed into the low satisfaction group. Multiple logistic regression analysis demonstrated that lower perceptions of receiving adequate information prior to transplantation (odds ratio [OR] = 0.17; 95% confidence interval [CI] = 0.079-0.379; p < 0.001), lower optimism according to the Life Orientation Test (OR = 1.24; 95% CI = 1.045-1.470; p = 0.014), and increased serum creatinine levels in the paired recipient (OR = 0.05; 95% CI = 0.250-1.011; p = 0.054) independently increased the odds of having less satisfaction with donation. Conclusions Our findings suggest that careful pre-donation education and more detailed informed consent may be needed, especially in LKDs with low constitutional optimism.